2020
DOI: 10.1177/1526924820913505
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Use of Diuretics After Kidney Transplantation Showed Increase in Delayed Graft Function

Abstract: Purpose: In acute renal injury, diuretics are widely considered to be harmful. Nevertheless, they are used frequently after kidney transplantation. We hypothesized that diuretics administered in the early postoperative treatment after kidney transplantation increase the incidence of delayed graft function (DGF). Methods: In this monocentric, retrospective cohort analysis, we screened the closed files of all consecutive patients who underwent kidney transplantation from 2011 to 2017. The outcome variable was DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Despite some understanding about clinical factors promoting DGF, many issues remain poorly understood. Recently, in retrospective analyses similar to ours, early use of diuretics or large volumes of intravenous normal saline solution were reported to be associated with DGF [11,12]. In contrast, Chaumont et al [10] reported the absence of perioperative saline loading as predisposing to DGF.…”
Section: Discussionsupporting
confidence: 61%
“…Despite some understanding about clinical factors promoting DGF, many issues remain poorly understood. Recently, in retrospective analyses similar to ours, early use of diuretics or large volumes of intravenous normal saline solution were reported to be associated with DGF [11,12]. In contrast, Chaumont et al [10] reported the absence of perioperative saline loading as predisposing to DGF.…”
Section: Discussionsupporting
confidence: 61%
“…However, more recent studies, such as the study conducted by Baar et al, found a significant relationship between the use of diuretics during kidney transplantation and the incidence of DGF. Therefore, the use or non-use of diuretics in kidney transplantation remains a controversial issue (27,28). Studies that have attempted to predict GFR in transplanted kidneys by using the amount of diuresis have shown that only measuring the amount of diuresis is not enough to predict the one-year performance of the transplanted kidney (29).…”
Section: Discussionmentioning
confidence: 99%